Discovery of FXR/PPARγ dual partial agonist. (1st May 2023) - Yamashita, Yukiko; Gohda, Keigo; Iguchi, Yusuke; Fujimori, Ko; Oda, Keisuke; Masuda, Arisa; Une, Mizuho; Teno, Naoki
Graphical abstract: Abstract: Farnesoid X receptor (FXR) and peroxisome proliferator-activated receptor (PPAR)γ are nuclear receptor 1 superfamily of transcription factors. FXR and PPARγ agonists have been individually investigated in clinical trial of anti-diabetic agents in the patients with nonalcoholic fatty liver disease (NAFLD). Regarding recent agonist development, the partial agonists for FXR and PPARγ are drawing attention from the standpoint of avoiding overactive responses caused by full agonists. In this article, we report that 18 with a benzimidazole scaffold possesses FXR/PPARγ dual partial agonistic activity. In addition, 18 shares the ability to reduce cyclin-dependent kinase 5-mediated phosphorylation of PPARγ-Ser273 and the metabolic stability in mouse liver microsome assay. To date, there are no published reports on FXR/PPARγ dual partial agonists with biological profiles similar to 18. Thus, the analog would be a feasible candidate as an unprecedented approach to NAFLD associated with type 2 diabetes mellitus.